ANCIENT JAPANESE MYTHOLOGY AS A BASIS FOR THE MENTALITY OF THE NATION AND OF THE POLITICAL SYSTEM - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Investigated the features of the initial stage of the formation of the ancient Japanese mythology. Highlighted the major mythological ideas, based on which further formed part of the political consciousness of the society and the specific features of the mentality, the image of the emperor and the power, relationship between government and society. Determined the dependence of mythological subjects from the political strategy of power.